2005
DOI: 10.1681/asn.2005020142
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Prevents Podocyte Apoptosis Induced by Puromycin Aminonucleoside

Abstract: Nephrotic-range proteinuria is due to glomerular diseases characterized by podocyte injury. Glucocorticoids are the standard of care for most forms of nephrotic syndrome. However, the precise mechanisms underlying the beneficial effects of glucocorticoids on podocytes, beyond its general immunosuppressive and anti-inflammatory effects, are still unknown. This study tested the hypothesis that the synthetic glucocorticoid dexamethasone directly reduces podocyte apoptosis. Growthrestricted immortalized mouse podo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
150
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(161 citation statements)
references
References 50 publications
10
150
0
1
Order By: Relevance
“…Importantly, we found a very low rate of the APOL1 polymorphism in our donor cohort, suggesting that donor APOL1 may play a local role in HIVAN pathophysiology, as was also suggested by the recent report of kidney APOL1 expression in normal and pathologic conditions. 26 Besides genetic predisposition, we cannot exclude that immunosuppressive drugs, by either interacting with the immune system or directly with podocytes (calcineurin inhibitors 27 and steroids 28 ), may modify the classical pattern of kidney lesions observed with HIV-1.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we found a very low rate of the APOL1 polymorphism in our donor cohort, suggesting that donor APOL1 may play a local role in HIVAN pathophysiology, as was also suggested by the recent report of kidney APOL1 expression in normal and pathologic conditions. 26 Besides genetic predisposition, we cannot exclude that immunosuppressive drugs, by either interacting with the immune system or directly with podocytes (calcineurin inhibitors 27 and steroids 28 ), may modify the classical pattern of kidney lesions observed with HIV-1.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, podocyte foot processes consist of cortical actin filaments and actin-associated proteins, which ensure the dynamic maintenance and reorganization of the cytoskeleton. In vitro studies have shown the direct effects of glucocorticoids on podocytes by protection of cultured podocytes via actin filament stabilization and prevention of apoptosis [60,61]. The effect on apoptosis [61] and upregulation of nephrin [59] appeared to be dose-dependent, which might be an explanation for the observed differences in clinical response to glucocorticoids.…”
Section: Nephrotic Syndromementioning
confidence: 99%
“…In vitro studies have shown the direct effects of glucocorticoids on podocytes by protection of cultured podocytes via actin filament stabilization and prevention of apoptosis [60,61]. The effect on apoptosis [61] and upregulation of nephrin [59] appeared to be dose-dependent, which might be an explanation for the observed differences in clinical response to glucocorticoids. Another in vitro study, performed by Guess et al, demonstrated functional glucocorticoid signaling by multiple glucocorticoid-induced responses, including downregulation of the GR [62].…”
Section: Nephrotic Syndromementioning
confidence: 99%
“…42 Moreover, recent studies have shown that corticosteroid treatment may have direct effects on podocytes. 43,44 In contrast, the clinical response to immunosuppression therapy in focal segmental glomerular sclerosis is different according to the podocyte number. 45 We, therefore, postulated that it was not the severity of the proteinuria at diagnosis but rather the dynamic change of proteinuria during treatment and follow-up that is a more important predictor for the outcome of IgAN.…”
Section: Discussionmentioning
confidence: 99%